Flavonoids with chemotaxonomic significance from Cajanus scarabaeoides. (December 2020) - Lan, Yu-Hsuan; Chiang, Yi-Ting; Lin, I-Ling; Huang, Shyh-Shyun; Lin, Yi-Hui; Lin, Yu-Chi
Abstract: Phytochemical investigation of Cajanus scarabaeoides (L.) Thouars (Fabaceae) led to the isolation of six compounds. The chemical structures of all compounds were determined by spectroscopic methods. All isolates were reported from this species for the first time. The presence of these compounds is consistent with the chemical classes reported from other members of the genus Cajanus . In summary, this study reported six compounds isolated from Cajanus scarabaeoides and discussed the plant chemotaxonomy of Cajanus genus. Highlights: Six compounds (1 –6 ) were first isolated from C. scarabaeoides. It is the first report of isolation of compounds 3 and 6 from the genus Cajanus. This is the first chemical investigation of C. scarabaeoides. These compounds provide evidence for chemotaxonomic studies of C. scarabaeoides and the genus Cajanus.